Peningkatan Kemampuan Berpikir Logis Anak Usia Dini Melalui Permainan Loose Part - Ati Winarti; Ema Aprianti (IKIP Siliwangi, 2026)
This research was motivated by logical thinking abilities of children in group B in Kober Raudhatul Jannah which had not been achieved, where children experienced difficulties in abstract reasoning, paling solutions to problems, understanding cause and effect relationships, as well as ini complex logical reasning suc as generalization an inference. This because teachers olny usemanufactured APE. The research aims to improve the logical thinking abilities of young children through loose part game media. This type of research is Classroom Action Research (PTK), where the teacher is the implementer of the learning while the researcher is the observer. This research design uses the Kemmis and Mc model. Taggart. This research was carried out in Kober Raudhatul Jannah. The subjects of this research consisted of 18 children in group B. Data collection techniques use observation and interviews. Data is analyzed descriptively and presented in the form of tables and graphs using words in narrative form which aims to explain the activities carried out during learning activities. The research results showed an increase in logical thinking abilities based on the evaluation of cycle I and cycle II. This shows that the ability to think logically can be carried out through learning activities using loose part media, where children are able to plan, arrange numbers, group, make shapes, make patterns and sort materials according to the level of learning achievement in children's cognitive development.